A forested tract-size profile of Florida's NIPF landowners - Thompson, Michael T. (USDA Forest Service, Southern Research Station, 1999)
Information gathered from 2,713 permanent Forest Inventory and Analysis (FIA) sample plots showed that over 1.0 million acres, or 15 percent of the nonindustrial private forest (NIPF) timberland in Florida is in forested tracts 10 acres or less.
Keywords: Statistik; Forests and forestry -- Florida -- Statistics; Fläche; Privatwald; Florida